2015
DOI: 10.1155/2015/890968
|View full text |Cite
|
Sign up to set email alerts
|

New Derivatives of Pyridoxine Exhibit High Antibacterial Activity against Biofilm-EmbeddedStaphylococcusCells

Abstract: Opportunistic bacteria Staphylococcus aureus and Staphylococcus epidermidis often form rigid biofilms on tissues and inorganic surfaces. In the biofilm bacterial cells are embedded in a self-produced polysaccharide matrix and thereby are inaccessible to biocides, antibiotics, or host immune system. Here we show the antibacterial activity of newly synthesized cationic biocides, the quaternary ammonium, and bisphosphonium salts of pyridoxine (vitamin B6) against biofilm-embedded Staphylococci. The derivatives of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 35 publications
0
31
0
1
Order By: Relevance
“…We investigated whether Ficin is able to disrupt bacterial biofilms formed by S. aureus and S. epidermidis , the bacteria colonizing wounds and thus retarding wound healing30. To do so, the bacteria were grown in BM broth earlier developed3132 for 72 h on 24-well TC-treated plates that provided a representative and repeatable formation of the rigid biofilm strongly attached to the surfaces, in contrast to Müller-Hinton broth, Trypticase soy broth or LB-medium (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…We investigated whether Ficin is able to disrupt bacterial biofilms formed by S. aureus and S. epidermidis , the bacteria colonizing wounds and thus retarding wound healing30. To do so, the bacteria were grown in BM broth earlier developed3132 for 72 h on 24-well TC-treated plates that provided a representative and repeatable formation of the rigid biofilm strongly attached to the surfaces, in contrast to Müller-Hinton broth, Trypticase soy broth or LB-medium (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports indicate that 2‐methyl tetrahydro‐3‐furanone and 4‐nitropyridine‐n‐oxide have anti‐biofilm activity (Kayumov et al, ; Rasmussen, Bjarnsholt, et al, ). Given this, we tested 2‐methyl tetrahydro‐3‐furanone and 4‐nitropyridine‐n‐oxide molecules for biofilm activity in our assay system, and our results showed that these molecules indeed showed anti‐biofilm activity, but through bactericidal route, that is, they killed the bacteria (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports indicate that 2-methyl tetrahydro-3-furanone and 4-nitropyridine-n-oxide have anti-biofilm activity (Kayumov et al, 2015;. Given this, we tested FIGURE 3 Pigment production inhibition by chemical derivatives in Chromobacterium violacium ATCC 12472 (a) and P. aeruginosa PAO1 (b).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Aliquots (500 L) of antimicrobials solutions with concentrations between 1 and 16 MBC in fresh BM buffer were added to the wells, and cultivation was continued for 24 hours at 37 ∘ C. To evaluate the viability of biofilm-embedded cells, the wells were washed several times with sterile phosphate-buffered saline (PBS) to remove nonadherent and detached cells. The washed biofilms were suspended in PBS by scratching the well bottoms with following treatment in a sonicator bath for 2 min at 20 kHz to favor the disintegration of bacterial clumps, and viable cells were counted by a drop plate method with minor modifications [27,28]. The serial 10-fold dilutions of each well were prepared and a 5 L aliquot of the suspension was dropped onto LB agar plates.…”
Section: Activity Against Bacterialmentioning
confidence: 99%
“…According to our recent report, quaternary ammonium pyridoxine derivatives are able to penetrate the bacterial biofilms and efficiently eradicate them [28]. Therefore, it was Journal of Chemistry 13 interesting to evaluate capability of 4b to target the biofilmembedded bacterial cells.…”
Section: Antibacterial Activitymentioning
confidence: 99%